Consumers' Perceptions and Expectations of Service Quality in Selected Fast Food Restaurants - Arumugam, Nalini (2001)
In Malaysia, fast food restaurants have experienced high growth rates and have introduced more new products and services. As a result, the level of competition has increased. Now, the issue is how each individual restaurant will maintain its competitiveness in terms of service quality. The study examines consumers' perceptions and expectations of service quality in selected fast food restaurants. The service quality scale called SERVQUAL measured consumers' perceptions and expectations. SERVQUAL consists of five dimensions of service quality, which are tangible, reliability, assurance, empathy and responsiveness. The SERVQUAL technique provides an overall measure of quality across all the five dimensions of service quality. In this study, 20 pairs of questions were used. One question from each pair asked consumers' to describe their expectation while the other question asked for their perceptions. A total of 456 consumers were selected as respondents. Frequency counts and percentages were used to analyze the demographic characteristics of the respon dents. Gap analysis was used to identify the differences between the consumers' perceptions and expectations. Factor analysis was used to examine the underlying pattern of the statements in the 20 items of the SERVQUAL scale. The study shows that the reliability dimension constituted the lowest score on the SERVQUAL scale. This was followed by the empathy, tangible and assurance dimensions. The factor analysis results identified six factors that affect consumers' perceptions and expectations of service quality. These six factors are reliability, customer care, customer service, company-oriented item, visionary and caring.